IPTEKS SISTEM PENATAUSAHAAN BARANG MILIK DAERAH PADA BADAN PENDAPATAN DAERAH PROVINSI SULAWESI UTARA - Oroh, Yosua Heleluya; Wokas, Heince R.N (Universitas Sam Ratulangi, 2020)
Regionally owned goods are goods that purchased or become a burden of the regional budget. The APBD is also obtained from the Regional Revenue, which includes Regional Taxes, Regional Levies, Results of Regional Wealth Management, and other revenues, in other words from the hands of the people. Regional property must be managed properly and correctly and must also comply with existing regulations. The regional revenue agency of North Sulawesi Province is an agency that manages income through motor vehicle tax and also retribution. Even the regional revenue agencies also have regional assets. It is important to administer proper regional property according to PERMENDAGRI No. 19 of 2016 concerning guidelines for the management of regional property.